PREVENTION OF ENZYMATIC BROWNING IN FRUIT AND VEGETABLES - Irina Ioannou (European Scientific Journal, ESJ, 2013)
Enzymatic browning is the second largest cause of quality loss in fruits and vegetables. Methods to prevent browning are the subject of a great deal of research in the field of the food industry. In this paper we review all the methods to prevent oxidation in fruit and vegetable. Studies developed along the last decade, like as chemical, physical (blanching, freezing), controlled atmosphere and coating methods, to prevent enzymatic browning are reported and discussed.